Development of the SIPANDA Archival Management Website for BKPSDM Sukabumi Regency - Firdaus, Muhamad Fahraz; Somantri, Somantri (Society : Jurnal Pengabdian Masyarakat, 2026)
The management of personnel archives at the Civil Service and Human Resources Development Agency (BKPSDM) of Sukabumi Regency was still conducted manually, leading to several challenges such as long document retrieval times, limited physical storage, high risk of document loss or damage, and difficulties in monitoring archive status. These issues reduced administrative efficiency and increased the workload of archive staff. To address these problems, a community engagement activity was conducted through the development and implementation of the SIPANDA (Regional Personnel Archive Management System). The system was developed using a structured software development approach and implemented in collaboration with archive management staff to ensure alignment with institutional needs. SIPANDA enables digital storage, archive classification, metadata management, and role-based access control to support secure and efficient archive management. The results of the implementation showed significant improvements in archive organization and accessibility, reduced document retrieval time, and enhanced data security and accountability. User evaluation indicated that the system was easy to use and effectively supported daily administrative activities. Overall, the community engagement activity successfully contributed to improving the efficiency and reliability of personnel archive management while supporting the digital transformation of public service administration at BKPSDM of Sukabumi Regency.